2020
DOI: 10.1186/s40352-020-00123-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers and facilitators to implementing advance care planning in prisons: a rapid literature review

Abstract: Background Limited information is available describing advance care planning (ACP) within correctional facilities, despite its increasing relevance due to the ageing population in prisons and the high rates of complex medical comorbidities. In Western countries, self-determination with respect to making future medical decisions is a human right that prisoners do not lose when they are remanded into custody. ACP enables individuals to plan for their health and personal care so their values, beliefs and preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“… 44 , 45 There are multiple barriers to performing ACP. Restrictive prison policies and the attitudes of carceral staff may obstruct the process of ACP 46 and there is evidence that physicians working in prisons and jails have limited knowledge of the role of ACP. 47 Additionally, incarceration prevents patients from accessing the social supports (friends and family) that many non-incarcerated people rely on when making health care plans, similar to how visitor restrictions have impacted goals of care discussions during this pandemic.…”
Section: Advanced Care Planning and Surrogate Decision Makingmentioning
confidence: 99%
“… 44 , 45 There are multiple barriers to performing ACP. Restrictive prison policies and the attitudes of carceral staff may obstruct the process of ACP 46 and there is evidence that physicians working in prisons and jails have limited knowledge of the role of ACP. 47 Additionally, incarceration prevents patients from accessing the social supports (friends and family) that many non-incarcerated people rely on when making health care plans, similar to how visitor restrictions have impacted goals of care discussions during this pandemic.…”
Section: Advanced Care Planning and Surrogate Decision Makingmentioning
confidence: 99%
“…Although Advanced Care Plans are an important component of promoting choice in end‐of‐life decision‐making, these plans tend to not indicate palliative care measures, nor does the process of ACP completion and review allow for meaningful conversations around values, beliefs, and wishes at end of life (MacLeod et al, 2020). …”
mentioning
confidence: 99%
“…Although Advanced Care Plans are an important component of promoting choice in end-of-life decisionmaking, these plans tend to not indicate palliative care measures, nor does the process of ACP completion and review allow for meaningful conversations around values, beliefs, and wishes at end of life(MacLeod et al, 2020).3 In almost all public policy statements that refer to or describe dying people's "needs" for formal service or support, these needs, and access to service, are described as being identified by a health care worker or professional. In no cases was it suggested that people might have a need or requirement to die at home; in addition, to access formal services either at home or in an institutional setting, assessment of need was required.4 Referring to family as a unit of care is a family-focused approach to supporting families in the care of a family member and the preventions of caregiver-related stress and hardship(Luttik, 2020).…”
mentioning
confidence: 99%
“…identified similar attitudinal and knowledge‐based obstacles amongst prisoners and staff. They detected an overall dominance of barriers which included institutional restrictive policies, limited access to health records and medical infrastructure deficits (Macleod et al, 2020).…”
mentioning
confidence: 99%
“…They have more in common than not, the ethos and skill set underpinning both focusing on person‐centred communication that can address sensitive and potentially distressing issues. There is increasing evidence that patients with serious mental illness and cognitive impairment can participate in advance care planning and that the opportunity to discuss end of life care may be reassuring and therapeutic for some (Dragonetti, 2018), and that prisoners can do so too (Macleod et al., 2020), particularly when prisons have clear procedures, proactive education, and consistent instruction about what preferences are possible.…”
mentioning
confidence: 99%